Robotic assisted kidney transplantation - Modi, Pranjal (Medknow Publications & Media Pvt Ltd, 2014)
Kidney transplantation is the standard of care for patients with end stage renal disease. While open surgery remains the gold standard, minimally invasive surgery has recently been introduced for the recipient undergoing kidney transplantation. We review the evolution of techniques of minimally invasive surgery for kidney transplantation with specific emphasis on technical aspects of robotic assisted kidney transplantation.